JENIS-JENIS BAKTERI GRAM NEGATIF POTENSIAL PATOGENPADA IKAN KERAPU LUMPUR (Epinephelus tauvina) DI KERAMBA JARING APUNG PERAIRAN BELAWAN Potential Pathogens of Gram Negative Bacteria to Greasy Grouper (Epinephelus tauvina) in Floating Net Cages, Belawan - Prasetia Ajitama; Dwi Suryanto; Yunasfi Djayus (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
Greasy Grouper (E. tauvina) is a popular fish among Indonesian. Pest and disease of greasy grouper becomes one the most important factors of the success of the aquaculture of the Greasy Grouper. Greasy grouper with disease syimtomt were taken from Floating Net Cages (FNC) located in Belawan. This study aimed toobserve disease potential pathogenic bacteria,which infected the greasy grouper and was also foundin FNC. The study was conducted from May to August 2014 in SKIPM Laboratory of Class I Medan II. The isolation and characterization of the bacterial pathogen of the greasy grouper and FNC water was condacted using dilution methods. Three species of potential phatogenic bacteria were found i.e Aeromonas salmonicida, Edwardsiella ictaluri, and Vibrio harveyi.Keywords:Epinephelus tauvina, Floating Net Cages, Bacterial pathogens